Answer:
30
Step-by-step explanation:
Average rate of change=Δf(x)/Δx = [f(x2)-f(x1]/[x2-x1]
Δf(x)/Δx = [f(5)-f(1]/[5-1]
f(5)=5³-5=120
f(1)=1³-1=0
Δf(x)/Δx = [120-0]/[5-1]=120/4=30
S (3, 0)
C (5, 1)
W (4, -4)
Explanation
You take the first number and add 6 to it and you get the new number and then you take the second number and subtract 3 from it
S: -3 + 6 = 3
S- 3 - 3 = 0
C: -1 + 6 = 5
C: 4 - 3 = 1
W: -2 + 6 = 4
W: -1 - 3 = -4
Answer=60
Since the base of the prism is a right triangle, we can use the pythagorean theorem to solve for x.
a²+b²=c²
plug in the data
a²+24²=30²
a²+576=900
subtract 576 from both sides
a²=324
sq root
a=18
So x=18
The formula for the volume of a triangular prism is...
V=(area of the base)*(height)
V=1/2bh*H where b=base of triangle h=height of triangle, H=height of prism
plug in the data that we know
720=1/2*18*24*H
720=216*H
divide both sides by 216
3 1/3=H
So x=18 and y=3 1/3 or 3.33 repeating
The product of the two
18*3 1/3=60
Answer=60
Answer: D
Step-by-step explanation:
All of it’s angles are equal